Immune neuroendocrine phenotypes in Coturnix coturnix: Do avian species show LEWIS/FISCHER-like profiles? - Nazar, Franco Nicolas (2015)
Immunoneuroendocrinology studies have identified conserved communicational paths in birds and mammals, e.g. the Hypothalamus-Pituitary-Adrenal axis with anti-inflammatory activity mediated by glucocorticoids. Immune neuroendocrine phenotypes (INPs) have been proposed for mammals implying the categorization of a population in subgroups underlying divergent immune-neuroendocrine interactions. These phenotypes were studied in the context of the LEWIS/FISCHER paradigm (rats expressing high or low pro-inflammatory profiles, respectively). Although avian species have some common immunological mechanisms with mammals, they have also evolved some distinct strategies and, until now, it has not been studied whether birds may also share with mammals similar INPs. Based on corticosterone levels we determined the existence of two divergent groups in Coturnix coturnix that also differed in other immune-neuroendocrine responses. Quail with lowest corticosterone showed higher lymphoproliferative and antibody responses, interferon-γ and interleukin-1β mRNA expression levels and lower frequencies of leukocyte subpopulations distribution and interleukin-13 levels, than their higher corticosterone counterparts. Results suggest the existence of INPs in birds, comparable to mammalian LEWIS/FISCHER profiles, where basal corticosterone also underlies responses of comparable variables associated to the phenotypes. Concluding, INP may not be a mammalian distinct feature, leading to discuss whether these profiles represent a parallel phenomenon evolved in birds and mammals, or a common feature inherited from a reptilian ancestor millions of years ago.